Biotic interactions and seed deposition rather than abiotic factors determine recruitment at elevational range limits of an alpine tree. (2nd July 2017) - Neuschulz, Eike Lena; Merges, Dominik; Bollmann, Kurt; Gugerli, Felix; Böhning‐Gaese, Katrin
Abstract: Abiotic factors, biotic interactions and dispersal ability determine the spatial distribution of species. Theory predicts that abiotic constraints set range limits under harsh climatic conditions and biotic interactions set range limits under benign climatic conditions, whereas dispersal ability should limit both ends of the distribution. However, empirical studies exploring how these three components jointly affect species across environmental gradients are scarce. Here, we present a study that jointly examines these factors to investigate the constraints of the recruitment of Swiss stone pine ( Pinus cembra ) at and beyond its upper and lower elevational range limits in the Swiss Alps. We investigated the natural recruitment of pines and additionally conducted seed transplant experiments to test how much abiotic factors (mean summer and winter temperatures, soil moisture), biotic interactions (understorey vegetation cover, canopy cover, seed predation) and/or seed deposition by the spotted nutcracker ( Nucifraga caryocatactes ) affect pine establishment. We found significant effects of biotic interactions and seed deposition by spotted nutcrackers on the recruitment of Swiss stone pine at both the upper and lower elevational range, but could not detect significant effects of abiotic factors. Importantly, dispersal limitation rather than temperature and soil moisture restricted the recruitment of pines at the upper elevational range. Synthesis . Our study highlights the importance of biotic interactions and dispersal ability in setting the upper range limits of species that have been regarded as mainly controlled by climate. This suggests that potential range shifts of plants in response to climate warming may strongly depend on seed dispersal and biotic interactions and not only on climatic factors. Abstract : In our study we show that biotic interactions and seed deposition, rather than abiotic factors, limit the recruitment of an alpine plant not only at lower elevational ranges but also at and beyond the tree line. These findings reveal that biotic interactions and seed dispersal might be more important for the dynamics of plant range expansions than previously assumed.